GREEN BANKING INITIATIVES FOR SUSTAINABLE DEVELOPMENT: PRACTICES AND PERFORMANCE OF COMMERCIAL BANKS - Mathur , Shaifali; Lakhani , Sakshee (Indian Journal of Finance and Banking, 2025)
Concerns about environmental sustainability and climate change have prompted commercial banks to adopt green initiatives, such as dedicated "Green Funds" and eco-friendly products, to support sustainable development. Regulatory frameworks and stakeholder pressures are driving banks to integrate environmental responsibility and corporate social responsibility into their operations. Green banking is defined as integrating environmentally friendly practices, such as sustainable lending, carbon footprint reduction, and financing for renewable energy, into banking operations. Standard practices include funding eco-friendly projects and minimizing the bank’s carbon footprint. These initiatives aim to align financial activities with ecological conservation and long-term economic stability. This study examines green banking practices across 10 commercial banks (5 public, 5 private) in Jaipur, India, focusing on their impact on banks’ environmental Performance. A survey using structured questionnaires collected data from 161 bank employees (including branch managers, branch heads, relationship managers, and assistant managers) across all ten banks. Subsequently, correlation and regression analysis were conducted to assess the relationship between green practices and environmental performance indicators. The results reveal a statistically significant and positive impact of green banking on the environmental Performance of both public and private sector banks. Quantitatively, the regression model explains about 71.3% of the Variance in the ecological performance measure (R² =0.713), indicating that sustainability-oriented practices substantially improve outcomes. The major finding is that green banking initiatives alone account for roughly 71.3% of the variation in banks’ environmental outcomes in this sample. Overall, these results highlight the strong empirical association between banks’ green initiatives and their environmental Performance. JEL Classification Codes: G21, G41, E44.